Diagnosis and treatment of anterior canal benign paroxysmal positional vertigo. (2nd September 2018) - Ling, Xia; Li, Kang-Zhi; Shen, Bo; Si, Li-Hong; Hong, Yuan; Yang, Xu
Abstract: Objective: To investigate the diagnosis and treatment of anterior canal benign paroxysmal positional vertigo (AC-BPPV). Design: Retrospective analysis of clinical data regarding the diagnosis and treatment of patients with AC-BPPV. Study sample: Six patients with AC-BPPV. Results: All patients underwent the Dix–Hallpike test and/or the straight head-hanging test to induce vertigo and down-beating nystagmus with or without torsional components. Down-beating nystagmus in patients 1, 3 and 6 lasted <1 min and was successfully treated with the Yacovino manoeuvre. Down-beating nystagmus in patients 2, 4 and 5 lasted >1 min. The Yacovino manoeuvre was not effective in patient 4, whereas it was effective in patient 2 but with frequently recurring symptoms. Patients 3, 4 and 6 also had other types of typical BPPV. Canal conversion appeared in patients 4 and 5 during the follow-up period. Conclusion: Typical BPPV, canal conversion, a therapeutic diagnosis after applying the Yacovino manoeuvre, and the follow-up outcome contribute to AC-BPPV diagnosis in patients with dizziness and vertigo presenting with down-beating positional nystagmus. Yacovino manoeuvre was more effective in AC-BPPV patients with down-beating positional nystagmus lasted <1 min than in those in whom it lasted >1 min.